Pengaruh Metode Latihan Komando terhadap Kemampuan Teknik Dasar Bolabasket - Sari Mariati; Desi Purnama Sari (Jurusan Kepelatihan, Fakultas Ilmu Keolahragaan, Universitas Negeri Padang, 2021)
The problem that arises in this study is the lack of basic technical skills for basketball athletes Junior Men's Galaxy Club, Padang Panjang City. This study aims to explain the effect of the commando training method on the basic technical skills of basketball in junior male athletes of the Galaxy club, Padang Panjang City. This type of research is a quasi-experimental method, with a population of 33 athletes. The sample was drawn using purposive sampling technique, in order to obtain a sample of 15 junior athletes. The instruments used were the dribbling test, ranzig-zag, passing and under basketball tests. Data were analyzed using parametric statistics through the t-test formula at 0.05α significance. The results showed: there was an effect of the command training method on the basic technique of basketball for junior male athletes of the Galaxy City Padang Panjang club, (t-hit 11.07> t-tab 2.145). The commando training method can be given to athletes to improve the basic technical skills of basketball, the command method emphasizes that the trainer is more skilled in providing training programs so that they can have good basic technical skills.